2015
DOI: 10.1159/000430231
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Activity of Meconopsis Horridula Hook, a Traditional Tibetan Medical Plant, in Murine Leukemia L1210 Cells

Abstract: Background: Meconopsis horridula Hook (M. horridula) has been used as a traditional Tibetan medicine to relieve heat and pain as well as mobilize static blood, and it is recognized as a good treatment for bruises. This study is the first trial to evaluate the tumor inhibitory activity of M. horridula extract and its underlying mechanism in the hope of providing evidence to support the anticancer function of M. horridula. Methods and Results: M. horridula extract was cytotoxic to L1210 cells in a dose- and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Oxidative stress plays important roles in regulating apoptosis of leukemia cells [36, 37]. Previous studies have demonstrated that elevated ROS are involved in TPEN-induced apoptosis of human acute lymphoblastic leukemia (ALL) cells [38].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress plays important roles in regulating apoptosis of leukemia cells [36, 37]. Previous studies have demonstrated that elevated ROS are involved in TPEN-induced apoptosis of human acute lymphoblastic leukemia (ALL) cells [38].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many Chinese herbs have gradually been identified as potential sources of antitumor drugs for its role in killing tumor cells less intensively and more naturally [6][7][8]. Huang Qi Huai (HQH) granules, with the brand name Huan Er Jin is primarily composed of trametes robiniophila murr (Huaier), Chinese wolfberry fruit and polygonatum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Meconopsis horridula Hook. f. & Thomson ethanol extract induced murine leukemia L1210 cell apoptosis and inhibited proliferation through G2/M phase arrest, and ROS were involved in the process ( Fan et al., 2015b ). Gallic acid, 3,4,5-trihydroxybenzoic acid ( Figure 3 ), which can be found in various natural products, such as green tea, grapes, Punica granatum L., P. emblica , Galla chinensis Mill., and many other fruits plants.…”
Section: Resultsmentioning
confidence: 99%